Junggo qäšqär tori (2016)
Das ist eine Regierungswebseite der Bezirksregierung des Bezirks Kashgar in Xinjiang der Volksrepublik China. Auf dieser Kategorie dieser Webseite werden Beiträge und Nachrichten über die Fachkräfte und Personen aus anderen chinesischen Provinzen publiziert. Im Jahre 2010 hat die KP Chinas ein "Entwicklungsprojekt" mit dem Motto "Xinjiang zu helfen" ins Leben gerufen. Laut diesem Projekt schicken andere 19 Provinzen Chinas Personen und Firmen nach Xinjiang, die an der "Entwicklung" und "Verwaltung" von Xinjiang beteiligen werden. - This is a government website of the Kashgar District Government of Kashgar County in Xinjiang, People's Republic of China. This category of this website publishes articles and news about the professionals and people from other Chinese provinces. In 2010, the CP of China launched a "development project" with the motto "To help Xinjiang". According to this project, other 19 Chinese provinces are sending people and companies to Xinjiang to participate in the "development" and "administration" of Xinjiang.